2022
DOI: 10.3389/fimmu.2022.909027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Atezolizumab for Advanced Non-Small Cell Lung Cancer Based on Clinical and Molecular Features: A Meta-Analysis

Abstract: ObjectiveAtezolizumab is becoming a significant therapy for non-small cell lung cancer (NSCLC), but its efficacy needs to be further improved. The aims of this study are to clarify the potency of atezolizumab-based therapy in advanced NSCLC patients with different clinical and molecular features, and to choose a better therapeutic regimen of atezolizumab to achieve more precise treatment in immunotherapy.MethodsRandomized clinical trials (RCTs) in the Cochrane Library, PubMed, Embase Science Direct, and Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“… 21 Similar results were also reported by Liu et al; they found that decreased immunotherapy response and shortened PFS were observed in NSCLC patients with liver metastasis. 38 Our findings are in accordance with the above results. For patients with liver metastasis, the risk of death is reduced by 18%, while it is 27% for those without liver metastasis.…”
Section: Discussionsupporting
confidence: 93%
“… 21 Similar results were also reported by Liu et al; they found that decreased immunotherapy response and shortened PFS were observed in NSCLC patients with liver metastasis. 38 Our findings are in accordance with the above results. For patients with liver metastasis, the risk of death is reduced by 18%, while it is 27% for those without liver metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of PD-1/PD-L1 blockade therapy differs significantly between PD-L1-positive and PD-L1-negative patients (31). The expression of PD-L1 is currently one of the most important predictive biomarkers, and the detection of PD-L1 expression in the tumor environment by IHC is the 99m Tc-PDA uptake in MC38-B7H1 tumors (A) and comparison of 99m Tc-PDA in tumor to tissue (B).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between immunotherapy and driver mutations has long been a research hotspot. A previous meta-analysis study showed that immunotherapy could not enhance overall survival (OS) or progression-free survival (PFS) in EGFR -mutant patients ( 26 ). At the same time, IMpower 150 reported a prolonged OS in EGFR -mutated patients with atezolizumab plus chemotherapy and bevacizumab ( 27 ).…”
Section: Discussionmentioning
confidence: 99%